English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

The problem is 4x(squared) + 2x - 1 = 0

Choices for answer:

-1+/- (square root)5

(-1+/- (sqaure root)5) / 4 (4 on the bottom)

-1+/-2 (square root)5

(-1+/- 2 (square root)5)4

2006-11-25 14:05:13 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

1. Move the constant to the right side of the equation:
4x^2 + 2x = 1

2. Divide out the x^2 coefficient:
x^2 + 1/2x = 1/4

3. Divide the coefficient of x (in this case, 1/16) by 2 and square it, then add it to both sides:
x^2 + 1/2x + 1/16 = 5/16

4. Factor the left side of the equation to (x + a)^2, where a is the number you just squared:
(x + 1/4)^2 = 5/16

5. Take the square root of both sides, remembering that this will produce both a positive and a negative root:
x + 1/4 = +/-sqrt(5/16)

6. Move the constant on the left to the right and simplify:
x = -1/4 +/-sqrt(5/16) = -1/4 +/-(sqrt 5)/4 = (-1 +/- sqrt 5)/4

2006-11-25 14:11:19 · answer #1 · answered by bgdddymtty 3 · 1 0

4x² + 2x - 1 = 0
4x² + 2x = 1
x² + 1/2 x = 1/4
x² + 1/2 x + 1/16 = 1/4 + 1/16
(x + 1/4)² = 5/16
x + 1/4 = ±√5/4
x = (-1±√5)/4

2006-11-25 14:10:57 · answer #2 · answered by Jim Burnell 6 · 0 0

4x 2 2x 1

2016-10-16 00:30:19 · answer #3 · answered by ? 4 · 0 0

fedest.com, questions and answers